Ex vivo tracheomalacia model with 3D‐printed external tracheal splint. (17th August 2016) - Kaye, Rachel; Goldstein, Todd; Aronowitz, Danielle; Grande, Daniel A.; Zeltsman, David; Smith, Lee P.
Abstract : Objective: To design and evaluate an ex vivo model of tracheomalacia with and without a three‐dimensional (3D)–printed external tracheal splint. Study Design: Prospective, ex vivo animal trial. Methods: Three groups of ex vivo porcine tracheas were used: 1) control (unmanipulated trachea), 2) tracheomalacia (tracheal rings partially incised and crushed), and 3) splinted tracheomalacia (external custom tracheal splint fitted onto group 2 trachea). Each end of an ex vivo trachea was sealed with a custom‐designed and 3D‐printed cap; a transducer was placed through one end to measure the pressure inside the trachea. Although the negative pressure was applied to the tracheal lumen, the tracheal wall collapse was measured externally and internally using a bronchoscope. Each group had at least three recorded trials. Tracheal diameter was evaluated using ImageJ software (National Institutes of Health, Bethesda, MD) and was averaged between two raters. Results: Average tracheal occlusion percentage was compared using Student t test. The average occlusion was 31% for group 1, 87.4% for group 2, and 20% for group 3. Significant differences were found between the control and tracheomalacia groups ( P < 0.01) and the tracheomalacia and splinted tracheomalacia groups ( P < 0.01). There was no significant difference between the control and splinted tracheomalacia groups ( P = 0.13). Applied pressure was plotted against occlusion and regression line slope differed between the tracheomalacia (0.91) and control (0.12) or splinted tracheomalacia (0.39) groups. Conclusion: We demonstrate the potential for an ex vivo tracheomalacia model to reproduce airway collapse and show that this collapse can be treated successfully with a 3D‐printed external splint. These results are promising and justify further studies. Level of Evidence: N/A. Laryngoscope, 127:950–955, 2017